Effects of low energy availability on bone health in endurance athletes and high-impact exercise as a potential countermeasure: a narrative review - Hutson, M. J.; O`Donnell, E.; Brooke-Wavell, K.; Sale, C.; Blagrove, R. C. (Sports Medicine, 2021)
Endurance athletes expend large amounts of energy in prolonged high-intensity exercise and, due to the weight-sensitive nature of most endurance sports, often practice periods of dietary restriction. The Female Athlete Triad and Relative Energy Deficiency in Sport models consider endurance athletes at high-risk for suffering from low energy availability and associated health complications, including an increased chance of bone stress injury. Several studies have examined the effects of low energy availability on various parameters of bone structure and markers of bone (re)modelling; however, there are differences in findings and research methods and critical summaries are lacking. It is difficult for athletes to reduce energy expenditure or increase energy intake (to restore energy availability) in an environment where performance is a priority. Development of an alternative tool to help protect bone health would be beneficial. High-impact exercise can be highly osteogenic and energy efficient; however, at present, it is rarely utilized to promote bone health in endurance athletes. Therefore, with a view to reducing the prevalence of bone stress injury, the objectives of this review are to evaluate the effects of low energy availability on bone health in endurance athletes and explore whether a high-impact exercise intervention may help to prevent those effects from occurring.